2015
DOI: 10.5114/wiitm.2015.49521
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic repair of esophageal atresia with a distal fistula - lessons from the first 10 operations.

Abstract: IntroductionThoracoscopic esophageal atresia (EA) repair was first performed in 1999, but still the technique is treated as one of the most complex pediatric surgical procedures.AimThe study presents a single-center experience and learning curve of thoracoscopic repair of esophageal atresia and tracheo-esophageal (distal) fistula.Material and methodsFrom 2012 to 2014, 10 consecutive patients with esophageal atresia and tracheo-esophageal fistula were treated thoracoscopically in our center. There were 8 girls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our analysis clearly showed a learning curve that fit a logarithmic function curve well, which seems to be reasonable for the learning curve analysis for all other types of surgical skills. Nachulewicz et al reported that the learning curve was obviously visible in eight successive cases, although the duration of the operation did not diminish markedly . Lee et al also showed that the initial period of the learning curve was evident in their earlier 13 cases of thoracoscopic EA/TEF repair .…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis clearly showed a learning curve that fit a logarithmic function curve well, which seems to be reasonable for the learning curve analysis for all other types of surgical skills. Nachulewicz et al reported that the learning curve was obviously visible in eight successive cases, although the duration of the operation did not diminish markedly . Lee et al also showed that the initial period of the learning curve was evident in their earlier 13 cases of thoracoscopic EA/TEF repair .…”
Section: Discussionmentioning
confidence: 99%